An analysis of two styles of arm action in the vertical countermovement jump - Gutierrez-Davila, M.; Amaro, F. J.; Garrido, J. M.; Rojas, F. J. (Sports Biomechanics, 2014)
The aim of this study was to determine the effect of two arm swing techniques, the simultaneous arm swing and the early arm swing, on vertical countermovement jump performance and on the contribution of the arms to vertical movement at the centre of mass (CM) during the propulsion phase. Participants were 28 athletes practicing sports in which the vertical jump constitutes a basic ability. Ground reaction forces were recorded by a force platform and the sagittal plane motion was recorded by a video camera. Although at take-off the vertical velocity (2.7 ± 0.2 m/s for simultaneous technique vs. 2.8 ± 0.2 m/s for early technique; p = 0.040) and position (1.18 ± 0.06 m for simultaneous vs. 1.17 ± 0.05 m for early; p = 0.033) of the CM were significantly different, no difference was observed in jump height (1.56 ± 0.01 m in both techniques). The arm action differed during the initial and final propulsion phases in both styles but the accumulated vertical contribution was similar. The practical implication in sports is that the use of the arm-swing technique to reach the maximum jump height should be determined by tactical demands instead of the technical execution of the arms.